Measuring quality of life through synthetic indexes in localities of the municipality of Acapulco, Guerrero, Mexico - Juárez Romero, Octaviano; Cañedo Villareal, Roberto; Barragán Mendoza, María del Carmen (Población y Salud en Mesoamérica, 2016)
Objective: in this paper, we contrast different synthetic indexes that seek to improve the approach to measurement of the quality of life perceived by people. Methods: we took a sample of 220 people from different suburban communities from the municipality of Acapulco. Reduction of variables was done with the Principal Component Analysis technique; with it, we obtained three synthetic indexes (Sum, Global, ad DP2). Results: by comparing the obtained results, with the perception of the quality of life that people reported, we can conclude that the best approach to this perception is done by the synthetic index DP2, which achieves 39.1% of direct matches, especially, in the good and very good quality of life categories. Conclusions: these results show that 80.9% of survey respondents consider that their quality of life is between good and very good, while only 35% are located in these categories using the economic index. This fact allows us to corroborate that, at least in this case, the economic conditions do not define the survey respondents’ perception of quality of life.